Susceptibility of Lion's paw scallop (Nodipecten subnodosus) juveniles to a pirAB-positive Vibrio campbellii strain isolated from Litopenaeus vannamei shrimp affected by Acute Hepatopancreatic Necrosis Disease (AHPND) - Pretell Monzón, Krizia (2025)
Articulo desarrollado en el ámbito de la ciencias, orientada al estudio de Lion's paw scallop